Pengaruh Manajemen Risiko Pasar Terhadap Profitabilitas Bank: Studi Bank Syariah yang Terdaftar Di Bursa Efek Indonesia - Abadiyah, Fajriyatul (Universitas Islam Negeri Sunan Kudus, 2024)
This study aims to analyze and understand the effect of market risk management as measured by stock price, inflation, and BI-7days-RepoRate on the profitability of Islamic banks listed on the Indonesia Stock Exchange (IDX). This research method is included in descriptive quantitative research. The population used is all Islamic banks listed on the IDX. The data used in this study is secondary data obtained from quarterly financial statements and historical data on stock prices of Islamic banks listed on the Indonesia Stock Exchange for the observation period from Q12021-Q12023. The research model uses the Ordinary Least Square panel data regression analysis method through the Eviews 10 program. The results showed that partially, stock prices and inflation had a positive and significant effect on the profitability of Islamic banks, while BI-7days-RR had a negative and significant effect on the profitability of Islamic banks. While the results of simultaneous tests are known, the three independent variables in this study together affect the profitability variable of Islamic banks by 89% and the remaining 11% are influenced by other factors outside this research.